Interferon-beta affects mitochondrial activity in CD4+ lymphocytes: Implications for mechanism of action in multiple sclerosis. (September 2015) - Haghikia, Aiden; Faissner, Simon; Pappas, Derek; Pula, Bartosz; Akkad, Denis A; Arning, Larissa; Ruhrmann, Sabrina; Duscha, Alexander; Gold, Ralf; Baranzini, Sergio E; Malhotra, Sunny; Montalban, Xavier; et al.
Background: Whereas cellular immune function depends on energy supply and mitochondrial function, little is known on the impact of immunotherapies on cellular energy metabolism. Objective: The objective of this paper is to assess the effects of interferon-beta (IFN-β) on mitochondrial function of CD4 + T cells. Methods: Intracellular adenosine triphosphate (iATP) in phytohemagglutinin (PHA)-stimulated CD4 + cells of multiple sclerosis (MS) patients treated with IFN-β and controls were analyzed in a luciferase-based assay. Mitochondrial-transmembrane potential (ΔΨm) in IFN-β-treated peripheral blood mononuclear cells (PBMCs) was investigated by flow cytometry. Expression of genes involved in mitochondrial oxidative phosphorylation (OXPHOS) in CD4 + cells of IFN-β-treated individuals and correlations between genetic variants in the key metabolism regulator PGC-1α and IFN-β response in MS were analyzed. Results: IFN-β-treated MS patients exhibited a dose-dependent reduction of iATP levels in CD4 + T cells compared to controls ( p < 0.001). Mitochondrial effects were reflected by depolarization of ΔΨm. Expression data revealed changes in the transcription of OXPHOS-genes. iATP levels in IFN-β-responders were reduced compared to non-responders ( p < 0.05), and the major T allele of the SNP rs7665116 of PGC-1α correlated with iATP-levels. Conclusion: Reduced iATP-synthesis ex vivo and differential expression of OXPHOS-genes in CD4 + T cells point to unknown IFN-β effects on mitochondrial energy metabolism, adding to potential pleiotropic mechanisms of action.